2019
DOI: 10.1111/bph.14595
|View full text |Cite
|
Sign up to set email alerts
|

Loganetin protects against rhabdomyolysis‐induced acute kidney injury by modulating the toll‐like receptor 4 signalling pathway

Abstract: Background and Purpose: Acute kidney injury (AKI) is a rapid renal dysfunctional disease, for which no effective drugs or therapies are available to improve prognosis.Loganetin is a natural product with unknown bioactivities. Here, we identified a new protective effect and mechanism of Loganetin in a mouse model of AKI induced by rhabdomyolysis.Experimental Approach: AKI was induced using glycerol by i.m. injection in mice models. Thirty minutes and 24 and 48 hr after injection of glycerol, the mice received 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 54 publications
(59 reference statements)
1
9
0
Order By: Relevance
“…In other study, rhabdomyolysis was induced by exerting 3 kg of pressure for 8 h in rats, and treatment with TAK-242 reduced renal injury and decreased systemic inflammatory cytokines (IL-6 or TNF-α) [ 164 ]. In line with this data, other studies also reported that direct inhibition of the TLR-4/JNK/p38/NFκB pathway with curcumin and loganetin [ 165 , 166 ], reduced kidney injury and inflammation, as well as improved renal function in pre-clinical models of rhabdomyolysis [ 45 , 165 ]. However, there are contradictory results in the literature, since TLR4 antagonism with TAK-242 did not protect from rhabdomyolysis-mediated renal damage in other study [ 162 ].…”
Section: Tlrs and Akisupporting
confidence: 71%
“…In other study, rhabdomyolysis was induced by exerting 3 kg of pressure for 8 h in rats, and treatment with TAK-242 reduced renal injury and decreased systemic inflammatory cytokines (IL-6 or TNF-α) [ 164 ]. In line with this data, other studies also reported that direct inhibition of the TLR-4/JNK/p38/NFκB pathway with curcumin and loganetin [ 165 , 166 ], reduced kidney injury and inflammation, as well as improved renal function in pre-clinical models of rhabdomyolysis [ 45 , 165 ]. However, there are contradictory results in the literature, since TLR4 antagonism with TAK-242 did not protect from rhabdomyolysis-mediated renal damage in other study [ 162 ].…”
Section: Tlrs and Akisupporting
confidence: 71%
“…[ 39 ] reported gentamycin‐induced AKI was associated with the activation of renal p38. In addition, JNK activation was increased in rhabdomyolysis‐induced AKI [ 40 ]. However, the activation of p38 and JNK pathway was not involved in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Loganetin ( Figure 1A) is a natural product derived from C. officinalis. 20 We found that at the same concentration, the inhibition of cell viability of loganetin ( Figure 1B) on GC cells was about three times higher than that of loganin. Therefore, we focused on loganetin, investigating its potential synergy with 5FU on proliferation of human GC cell lines including HGC27 and MGC803.…”
Section: Synergistic Inhibitory Effects Of 5fu and Loganetin On Hummentioning
confidence: 71%
“…31 Recent work has revealed that loganetin protects against kidney injury in a TLR4-dependent manner. 20 However, the role of loganetin that plays in cancer was not previously known. Our data revealed that loganetin exhibits clear anti-tumour efficacy ( Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation